A uremic toxin, 3-carboxy-4-methyl-5-propyl-2-furanpropionate induces cell damage to proximal tubular cells via the generation of a radical intermediate - Miyamoto, Y.; Iwao, Y.; Mera, K.; Watanabe, H.; Kadowaki, D.; Ishima, Y.; Chuang, Victor; Sato, K.; Otagiri, M.; Maruyama, T. (Elsevier, 2012)
3-Carboxy-4-methyl-5-propyl-2-furanpropionate (CMPF), a furan fatty acid uremic toxin (UT) and a substrate for organic ion transporters, contributes to the accumulation of CMPF in renal tubular cells. Although oxidative stress induced by UTs has been proposed as a mechanism of its toxicity in chronic kidney disease, little information is available regarding the redox property of CMPF and its relation to renal cell damage. The findings herein show that CMPF enhances the production of reactive oxygen species (ROS) in HK-2 cells in the presence of angiotensin II (A-II), an inducer of O2˙−. When iron is also present, CMPF and A-II induce the Fenton reaction, resulting in a further increase in ROS production. Such CMPF-induced oxidative stress increases TGF-β1 secretion in HK-2 cells, and a positive correlation between CMPF-induced ROS production and the secretion of active TGF-β1 was observed. CMPF caused a reduction in cell viability which was negatively correlated with intracellular ROS production. These negative effects of CMPF in HK-2 cells were completely suppressed by probenecid, an inhibitor of organic anion transport. Interestingly, in vitro ROS assays indicate that CMPF directly interacts with superoxide anion radicals (O2˙−) and peroxy radicals (LOO˙) to produce CMPF radicals. The subsequent interaction of CMPF radicals with dissolved oxygen leads to the overproduction of O2˙−. Based on these findings, we conclude that CMPF, which accumulates in the renal cells, appears to play a prominent role as a pro-oxidant which subsequently leads to renal cellular damage via the overproduction of O2˙−.